Factors Inhibiting and Facilitating Japanese Teachers of English in Adopting Communicative Language Teaching Methodologies - Cook, Melodie (k@ta: A Biannual Publication on the Study of Language and Literature, 2010)
This is a partial report on junior and senior high school Japanese teachers of English and changes in their beliefs and practices after attending a 4-month program of language and pedagogical study in Canada. Findings from this case study suggest that this group of Japanese teachers could effectively apply what they had learned abroad if they were not bound by practical constraints, external influences, or if they were teaching specifically communication-oriented classes.